Development Strategy of Virgin Coconut Oil Bumdes in Collection: JEL Classification: I21, I28, I31, H52, C83 - Rusdan Rusdan; Mujahid Yunus; Sri Adrianti Muin (Newinera Publisher, 2026)
This study aims to analyze the development strategy of Virgin Coconut Oil (VCO) implemented by BUMDes Bersama Karang Unarang Sejahtera in Sebatik District. The main focus of this research is to identify supporting factors, inhibiting factors, and the strategies applied to optimize local potential through the VCO product. The method used is a descriptive qualitative approach, with data collection techniques including in-depth interviews, field observations, and documentation. Research informants included BUMDes managers, production workers, raw material suppliers, village government representatives, and local community members. The findings show that the VCO development strategy involves planning stages, community involvement, technical training, and gradual marketing through social media and local events. The main supporting factors are the abundant availability of coconut raw materials, government support, and active community participation. Meanwhile, the inhibiting factors include limited technology, constraints in digital marketing, and the underdevelopment of product legality. This research recommends increasing human resource capacity, continuous policy support, and expanding distribution networks to strengthen product competitiveness in broader markets.